????????????? ??????? ?? ?????? ??????? ? ??????????? ?????? ??? ????? ??????? - Aswari, Muhammad Danil; Wahyudi, Dedy; Ariadi, Lalu Muhammad (MODELING: Jurnal Program Studi PGMI, 2023)
This research is about contrast analysis and error analysis. The aim of this study is to find out the effectiveness of contrasting analysis and error analysis in improving the understanding of the Arabic language students in Madrasa Aliyah Addiinul Qayyim. This madrasah was chosen as an object of research because of the differences in the methods of teaching Arabic with other madrasas in Eastern Lombok. The hypothesis of this research is that contrast analyses and error analyses are effective in improving the ability of Arabic students. This research uses this kind of experiment with pretest and posttest designs as well as quantitative approaches. The total sample is a class of twenty students with data collection techniques using tests before and after as well as the test-t formula. Both the design of the pretes and the postest are established on the basis of the teaching instruments applied by the teachers in the madrasah of addiinul qayyim. The results of this study show that t-count is 4,769 and t-table is 2,061, which means that contrast analysis and error analysis are effective in improving students' skills in Arabic. Abstrak Penelitian ini tentang analisis kontrastif dan analisis kesalahan, tujuan dari penelitian ini adalah adalah untuk mengetahui efektivitas analisis kontrastif dan analisis kesalahan dalam meningkatkan pemahaman bahasa arab siswa pada kelas x madrasa aliyah addiinul qayyim. Madrasah ini dipilih menjadi obyek dari penelitian karena perbedaan metode pengajaran bahasa Arab dengan madrasah-madrasah lain di Lombok Timur. Hipotesis dari penelitian ini adalah bahwa analisis kontrastif dan analisis kesalahan efektiv untuk meningkatkan kemampuan bahasa arab siswa. Penelitian ini menggunakan jenis eksperimen dengan desain pretest dan postest serta pendekatan kuantitatif. Baik desain pretes, maupun postest, keduanya ditetapkan berdasarkan instrumen-instrumen pengajaran yang diterapkan oleh para guru di madrasah addiinul qayyim. Jumlah sampelnya adalah kelas x yang berjumlah dua puluh siswa dengn tehnik pengumpulan data menggunakan test sebelum dan sesudah serta menggunakan rumus uji-t . Hasil penelitian ini bahwa t-hitung 4,769 dan t-tabel 2,061 yang berarti bahwa analisis kontrastif dan analisis kesalahan efektiv dalam peningkatan kemampuan siswa di bidang bahasa Arab.